Modelo matemático logístico para aquecimento de toras de Eucalyptus grandis w. hill com vapor e água quente - Coneglian, Ademilson; Severo, Elias Taylor Durgante [UNESP]; Batista, Wagner Roberto; Pereira, Ismael Martins; Gomes, Ivana da Silva (My University, 2017)
The aims of this study was to obtain a mathematical logistics model that represents the best heating of logs of Eucalyptus grandis in function of the diameter and the length of the logs in the thermal treatments with steam and hot water. To this end, were collected 6 logs 30 trees to 32 years of age, from the Horto Florestal de Mandurí-SP, Brazil. Diameter classes of logs were 25 ⊣ 30 cm, 30 ⊣ 35 cm, 35 ⊣ 40 cm. In each of the logs were inserted three thermocouples with depths of 1/3, of the radius, 2/3 of the third beam, near the center thereof. Were used 15 heat-treated logs with steam at 85°C and 100% relative humidity, and 15 logs heated with hot water to the thermocouple reach 85° C of temperature at position 50 mm radius. It is concluded that the mathematical model set obtained a logistic behavior in the treatments steam and hot water, presents an optimal consumption of energy e technical feasibility in heating process of logs.
Mathematical model for heating of logs of logistic Eucalyptus grandis w. hill with steam and hot water
Keywords: Energy consumption; Heart transfer wood; Thermocouples